Agonists for Bitter Taste Receptors T2R10 and T2R38 Attenuate LPS-Induced Permeability of the Pulmonary Endothelium in vitro - Kertesz, Zsuzsanna; Harrington, Elizabeth O.; Braza, Julie; Guarino, Brianna D.; Chichger, Havovi (Frontiers in Physiology, 2022)
One of the hallmarks of acute respiratory distress syndrome (ARDS) is an excessive increase in pulmonary vascular permeability. In settings of ARDS, the loss of barrier integrity is mediated by cell-cell contact disassembly and actin remodelling. Studies into molecular mechanisms responsible for improving microvascular barrier function are therefore vital in the development of therapeutic targets for reducing vascular permeability seen in ARDS. Bitter taste receptors (T2Rs) belong to the superfamily of G protein–coupled receptors, found in several extraoral systems, including lung epithelial and smooth muscle cells. In the present study, we show for the first time that several T2Rs are expressed in human pulmonary arterial endothelial cells (HPAECs). Our results focus on those which are highly-expressed: T2R10, T2R14 and T2R38. Agonists for T2R10 (denatonium) and T2R38 (phenylthiourea), but not T2R14 (noscapine), significantly attenuated lipopolysaccharide (LPS)-induced permeability and VE-cadherin internalisation in HPAECs. In T2R10- or T2R38- siRNA knockdown cells, these endothelial-protective effects were abolished, indicating a direct effect of agonists in regulating barrier integrity. Our further findings indicate that T2R10 and T2R38 exert their barrier protective function through cAMP but via Rac1-dependent and independent pathways respectively. However, using an in vivo model of ARDS, the T2R38 agonist, phenylthiourea, was not able to protect against pulmonary edema formation. Taken together, these studies identify bitter taste sensing in the pulmonary endothelium to regulate barrier integrity in vitro through cAMP-Rac1 signalling.